1996
DOI: 10.1139/b96-073
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition along a bog to rich fen gradient in central Alberta, Canada

Abstract: The carbon (C) and nitrogen (N) contents and decomposition rates of the aboveground litter were measured in five peatlands (bog, poor fen, open moderately rich fen, wooded moderately rich fen, and lacustrine sedge fen) in central Alberta, Canada, over a period of 2 years. Decay rates and C and N content of the dominant species were measured at each site. Weight losses after 1 and 2 years were negatively correlated with initial and final C/N ratios. Weight losses were positively correlated with initial and fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
96
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(108 citation statements)
references
References 32 publications
9
96
3
Order By: Relevance
“…2) was comparable in magnitude to the impact of reduced water tables on in situ litter decomposition in south east Asia (Brady 1984) and boreal and temperate wetlands (Szumigalski and Bayley 1996;Haraguchi et al 2003;Williams and Yavitt 2003). The clear effect of the flooding treatment on ex situ mass loss rates suggests that litter decomposition at these sites may be highly sensitive to even small decreases in the height of the water table, which has important implications for the contribution of litter to long term C accumulation in tropical peatlands.…”
Section: Discussionmentioning
confidence: 76%
“…2) was comparable in magnitude to the impact of reduced water tables on in situ litter decomposition in south east Asia (Brady 1984) and boreal and temperate wetlands (Szumigalski and Bayley 1996;Haraguchi et al 2003;Williams and Yavitt 2003). The clear effect of the flooding treatment on ex situ mass loss rates suggests that litter decomposition at these sites may be highly sensitive to even small decreases in the height of the water table, which has important implications for the contribution of litter to long term C accumulation in tropical peatlands.…”
Section: Discussionmentioning
confidence: 76%
“…Decomposition of Sphagnum litter has been demonstrated to be enhanced, at least after 1 year of field burial, by low initial values of phenolics/nutrient and C/nutrient quotients [Szumigalski and Bayley, 1996;Limpens and Berendse, 2003;Dorrepaal et al, 2005;. On the basis of selected data, we observed that k values of Sphagnum litter were negatively correlated with initial AUR/N quotients (Pearson's r = -0.66; p < 0.05; n = 11; Figure 4).…”
Section: Litter Chemistrymentioning
confidence: 81%
“…Most of the variation in decomposition rates can be explained by litter quality, temperature and soil moisture (Berg et al, 1993;Walse et al, 1998). In pristine (undrained) peatlands, decomposition of similar litter materials is related not only to water level (e.g., Santelmann, 1992) but also to soil and/or soil water pH and base cation content (Verhoeven and Toth, 1995;Verhoeven et al, 1996;Szumigalski and Bayley, 1996) being generally faster in fens than bogs (Farrish and Grigal, 1988;Verhoeven et al, 1990). After permanent water level drawdown, these characteristics gradually change (Laine et al, 1995ab;Laiho et al, 1999).…”
Section: Introductionmentioning
confidence: 99%